Being stable and getting along with others: perceived ability expectations and employability among Finnish university students - Hannu Räty; Inna Kozlinska; Kati Kasanen; Päivi Siivonen; Katri Komulainen; Ulla Hytti (Springer, 2022)
The aim of this study was to examine what sort of ability expectations university students have about the requirements of working life, and how the perception of these expectations relate to students’ perceptions of their own employability. The participants comprised a sample of students (N = 1819) from two Finnish universities, representing diverse fields of study. They were asked to describe themselves according to a set of abilities and to then indicate those abilities that would be particularly important for them in the labour market. It was found that being stable and getting along with others were the most commonly considered generic capabilities for coping in working life. Furthermore, those university students who identified entrepreneurial skills and extroversion as predominant ability requirements were prone to have relatively pessimistic perceptions of their employability possibilities. Accordingly, the results of the study suggest that students’ views of their expected abilities tend to shape their perceptions of their employment prospects, particularly with regard to entrepreneurial skills.